Pengaruh Loan Deposit Ratio, Liquidity Reserve Requirement Ratio, Leverage dan Ukuran Perusahaan Terhadap Window Dressing (Perusahaan Perbankan Umum Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Santi Tyas Sasmita; Shinta Noor Anggraeny; RB. Iwan Noor Suhasto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the influence of Loan Deposit Ratio (LDR), Liquidity Reserve Requirement Ratio (LRRR), Leverage, and Company Size on Window Dressing. The independent variables in this research are Loan Deposit Ratio (LDR), Liquidity Reserve Requirement Ratio (LRRR), Leverage, and Company Size. The dependent variable in this research is Window Dressing. This research uses secondary data obtained from the company's annual financial reports and quarterly reports, accessed via the website www.idx.co.id. The population in this study was 46 conventional general banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Determining the sample for this research used purposive sampling based on certain criteria and obtained a sample of 40 conventional general banking companies. The data analysis technique was carried out using multiple linear regression using SPSS tools. The independent variables in this research are Loan Deposit Ratio (LDR), Liquidity Reserve Requirement Ratio (LRRR), Leverage, and Company Size. The results of this research are that company size influences Window Dressing. Meanwhile, Loan Deposit Ratio (LDR), Liquidity Reserve Requirement Ratio (LRRR), Leverage have no effect on Window Dressing